Meta-Analysis: The Effect of HBM-Based Health Education on Improving Oral Health in Students - Weni Irma Suryani; Point Haryanti; Iik Sartika (Journal of Health Promotion and Behavior, 2025)
Background: Oral health problems are an important concern in health development, one of which is caused by the vulnerability of school-age children from oral and dental health disorders. School age is an important age in the growth and physical development of children. One of them is the habit of maintaining oral and dental health. This study aims to analyze and estimate the influence of HBM-based health education on oral and dental health in students. Subject and Method: The meta-analysis was performed according to the flow of the PRISMA diagram and the PICO model. The search for articles in this study is through databases that include PubMed, Google Scholar, Science Direct and Scopus. With keywords including: "Oral health" AND "Health Belief Model" AND "Students". Full paper article with RCT study, the subject of the study is the student, the measure of the relationship used is SMD, the outcome of the research is knowledge and perception of the severity of obesity prevention. Analysis was done with Revman 5.3 Results: There were 6 articles with randomized control trial designs from Iran and Hong Kong with 829 research samples. A meta-analysis of 6 randomized control trial studies  concluded that students who received HBM-based education had a 1.04-fold higher perceived benefit for improving oral health compared to students who did not receive education, and the effect was statistically significant (SMD= 1.04; CI 95%= 0.28 to 1.79; p= 0.007). A meta-analysis of 5 randomized control trial studies  concluded that students who received HBM-based education had a higher perception of severity to improve oral health 1.73 times compared to students who did not receive education, and the effect was statistically significant (SMD= 1.73; CI 95%= 0.49 to 2.98; p=0.006). Conclusion: HBM-based education has benefit to improve oral health.